Blockchain-Enabled Cybersecurity In Banking Systems: A Survey Of Current Practices - Gautam, Parth (Journal of Global Research in Mathematical Archives(JGRMA), 2026)
The fast digitalization of bank services has exposed financial institutions in the global market to such cyber threats and thus, cybersecurity has become a burning issue in the financial sector. Conventional centralized security systems can hardly handle such issues as data corruption, fraud, identity theft, and system failure in response to more advanced cyberattacks. Here, blockchain technology has risen as a viable option to improve cybersecurity of banking systems because it has a decentralized, immutable, and cryptographically secured structure. The paper is a critical analysis of blockchain-based cybersecurity in the banking industry that analyzes the basic principles of blockchain technology, cybersecurity needs in banking system, and application of blockchain in security. The paper explains the possibility of providing confidentiality and integrity of data in addition to minimizing single point of failure through the use of distributed ledger technology and cryptographic methods. It also examines the use of blockchain in securing financial transactions, enhancing fraud detection and prevention, and providing the opportunity to manage the identity with the help of Know Your Customer (KYC) and Anti-Money Laundering (AML) compliance. The literature review outlines an in-depth research of blockchain-based security solutions, AI-based threat detection and classification of cyber threats in the banking setting. The results show that blockchain has the potential to substantially increase the levels of trust, transparency, and resilience in digital banking systems, but such issues as scalability, regulatory adherence, and large-scale usability still exist. The paper has ended by highlighting the possibilities of blockchain as a supplementary cybersecurity framework in current banking ecosystems